Issues and Prospects on the Movement of Natural Persons and Human Capital Development in the Philippine-American Economic Relations - Tereso S. Tullao; Michael Angelo A. Cortez (Philippine Institute for Development Studies (PIDS), 2006)
The United States of America is the top trading partner of the Philippines and also the top destination of highly skilled and professional Filipino workers. This paper explores the possibility of a free trade agreement (FTA) that covers the asymmetries of the two countries in labor, services and human resources development, particularly educational services. The existing FTAs of the U.S. were examined to seek for provisions the Philippines may adopt for a freer movement of natural persons. However, there are barriers inherent in the U.S. immigration and recent U.S. Congressional pronouncements to uphold the primacy of their immigration policy, thus, no more similar liberal agreements could be entered into. Issues on the movement of workers, particularly mutual recognition, accreditation, taxation and the refund of social security contributions were raised. For the educational sector, the issue of public subsidy and national treatment of foreign service providers were also brought up to clarify the objective of bringing access to students. The paper concluded that for an FTA concerning the movement of natural persons to materialize, the Philippines should weigh its sacrifices against what it will be requesting from the U.S. within the context of the overall importance of the maximizing opportunities for the Filipino worker.
Keywords: 330; trade liberalization; labor market; labor migration; market access; General Agreement on Trade in Services (GATS); movement of natural persons; services trade; modes of supply; educational system; cross-border transactions; reciprocity; preferential treatment; national treatment; mutual recognition agreement; free trade agreements (FTAs); Internationale Wirtschaftsbeziehungen; Freihandelszone; Dienstleistungshandel; Faktormobilität; Arbeitsmigranten; Handelsliberalisierung; Philippinen; USA